Renal dysfunction and heart failure - cardiorenal syndrome: a retrospective study at Charlotte Maxeke Johannesburg academic hospital - Zachariah, Don (My University, 2017)
INTRODUCTION The field of medicine has been challenged by the dual epidemic of heart failure and renal insufficiency. There is an increasing need to identify these patients at an early stage so as to delay progression to renal damage. Furthermore there is a lack of local data assessing the relationship between heart failure and renal dysfunction. AIMS • To identify the prevalence of renal dysfunction in patients attending the heart failure clinic at Charlotte Maxeke Johannesburg Academic hospital (Cardiorenal syndrome Type II) • To evaluate the relationship between severity of heart failure and severity of renal dysfunction • To compare heart failure with reduced ejection fraction (HFREF) variables between patients with and without renal dysfunction. METHODOLOGY This study is a single center retrospective study of patients attending Charlotte Maxeke Johannesburg Academic Hospital Heart Failure Clinic. Heart failure patients included in this study were those with an ejection fraction < 50% as this is an accepted definition for HFREF. Patients with HFREF were analyzed specifically for the following; presence of renal dysfunction, Ejection Fraction (EF), Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP), Haemoglobin (HB), New York Heart Association (NYHA) functional class, furosemide dose , six minute walk test (6MWT) and Minnesota Living with Heart Failure Questionnaire (MLFQ) score . Presence of renal dysfunction was identified based on the glomerular filtration rate (eGFR) value of less than 60ml/min/1.73m2 as this is the threshold eGFR below which complications of renal impairment appear. The eGFR was calculated using the Modification of Diet in Renal Disease (MDRD) abbreviated formula: (186.3 X serum creatinine) -1.154 x (age) -0.203 x (0.742 if female) x (1.212 if African) The control group consisted of patients attending the clinic who did not have renal dysfunction. RESULTS A total 242 files were reviewed. Forty-two files were excluded from the study due to lack of adequate study data recorded in the file. Data was collected and entered into a database, which was analyzed using the Statistics/Data Analysis Program (STATA) Version 10.0. The mean age of the study group was 53.3 years (SD± 15.05) with the youngest subject being 21 years old and the oldest subject aged 85 years. The mean SBP was 119mmHg and the mean DBP was 75mmHg. The mean eGFR was 72.01 ml/min/1.73m2. The overall prevalence of low eGFR (<60ml/min/1.73m2) in the sample population was 34.5 %. The prevalence in female and male patients with a low eGFR was 35% and 33.6% respectively. Analysis of MLFQ, 6MWT, DBP and age yielded a positive correlation with eGFR, which was statically significant (p<0.05). An insignificant correlation was obtained comparing eGFR with SBP (p=0.07), EF (p=0.69) and HB (p=0.79). The Analysis of Variance Test (ANOVA), showed a significant correlation between eGFR values across the different NYHA functional classes (p 0.012). Thus it was found that the higher the NYHA class (clinically worse) was associated with worse renal function. The mean eGFR for NYHA I was 77.05 ml/min/1.73m2, for NYHA II was 70.61 ml/min/1.73m2, for NYHA III was 64.13 ml/min/1.73m2 and NYHA IV was 50.02 ml/min/1.73m2. DISCUSSION The overall prevalence of low eGFR (<60ml/min/1.73m2) in this study was 34.5%, a finding consistent with international trials. The majority of patients in this study were in NYHA functional class I or II, thereby highlighting the fact that renal dysfunction is common in heart failure patients and starts early. Statistically significant values were also obtained between eGFR and 6MWT, MLFQ, furosemide dose, age and DBP. The patients with higher 6MWT have better effort tolerance, thereby classifying their heart failure as milder. This in effect confirms that higher eGFR patients have higher effort tolerance. Higher MLFQ scores and higher furosemide doses are inversely correlated to eGFR. The more subjective symptoms you have, and the higher doses of furosemide you need, is a reflection of the severity of the heart failure. With regards to age, there is a normal physiological decline in eGFR with increasing age. In this study a statistically significant negative correlation between eGFR and NYHA was found. Thus a higher NYHA class is associated with worse renal function. This suggests that the clinically more advanced the patient, the poorer the renal function. Also, the prevalence of low eGFR (<60ml/min/1.73m2) within each NYHA class, as expected, increased with increasing NYHA class. It was 27% for NYHA I, 38% for NYHA II, 40% for III, while class IV had 80% of low eGFR prevalence CONCLUSION The findings of this study confirm that the cardio-renal syndrome is common in a local cohort of heart failure patients. The study also suggests that renal dysfunction starts in the early stages of heart failure (NYHA I/II) and becomes more prevalent in patients with more advanced stages of heart failure. These findings highlight the need to treat heart failure patients early after presentation and more appropriately if we are to decrease complications such as renal dysfunction, thereby improving morbidity and mortality.
A Research report submitted to the Faculty of Health Sciences, Department of Internal Medicine, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the Degree of Master of Medicine in the Division of Cardiology. 2017
Keywords: Renal Dysfunction; Cardio-Renal Syndrome; Heart Failure